Effect of Aspalathus linearis supplementation, during anti-retroviral treatment, on the heart and aortas of male Wistar rats and the effects of drinking rooibos on the cardiovascular profile of patients on ART. - Imperial, Emiliana Gomes (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2017